Synergistic effects of ground granulated blast furnace slag and circulating fluidized bed fly ash in lime-activated cementitious materials - Xingyi Wang; Jinzhuang Lv; Jingchao Yang; Jiamin Zhu; Bin He; Xiaoyuan Wang; Pengju Han; Xiaohong Bai (Case Studies in Construction Materials)
Alkali-activated materials prepared from industrial solid wastes have excellent performance, advancing the cement industry towards achieving the Net-zero emissions goal. However, the diverse synergistic effects of various solid waste types necessitate further investigation. In this study, the effect of different content (20 %, 30 %, 40 %, and 50 %) of ground granulated blast furnace slag (GGBFS) on the mechanical performance of circulating fluidized bed fly ash (CFBFA)-GGBFS-lime ternary cementitious materials (CGL) was investigated. The synergistic mechanism of GGBFS and CFBFA was elucidated through analyses of hydration heat, XRD, FT-IR, and SEM-EDS tests. The results indicated that GGBFS facilitated sulfate consumption during the early hydration stage, promoting the dissolution of CFBFA. This, in turn, enhanced the availability of sulfate, calcium, and active silicon-aluminum phases for CGL hydration, ultimately leading to an improvement in their overall hydration degree. Conclusively, the optimal synergistic effect between CFBFA and GGBFS was observed at a GGBFS content of 40 %, with a compressive strength of 32.84 MPa at 28 days. However, excessive GGBFS content (50 %) could lead to the premature formation of a “hydration barrier membrane”, negatively affecting the sustained hydration of CGL. This work presented an eco-friendly approach to the resource utilization of CFBFA, particularly in terms of mineral resource consumption, and held promising prospects for applications in projects.